Anticarcinogenic impact of extracellular vesicles (exosomes) from cord blood stem cells in malignant melanoma: A potential biological treatment. Issue 2 (22nd December 2022) - Naeem, Parisa; Baumgartner, Adi; Ghaderi, Nader; Sefat, Farshid; Alhawamdeh, Maysa; Heidari, Saeed; Shahzad, Fanila; Swaminathan, Karthic; Akhbari, Pouria; Isreb, Mohammad; Anderson, Diana; Wright, Andrew; et al.
Abstract: Incidence of Malignant Melanoma has become the 5th in the UK. To date, the major anticancer therapeutics include cell therapy, immunotherapy, gene therapy and nanotechnology‐based strategies. Recently, extracellular vesicles, especially exosomes, have been highlighted for their therapeutic benefits in numerous chronic diseases. Exosomes display multifunctional properties, including inhibition of cancer cell proliferation and initiation of apoptosis. In the present in vitro study, the antitumour effect of cord blood stem cell (CBSC)‐derived exosomes was confirmed by the CCK‐8 assay ( p < 0.05) on CHL‐1 melanoma cells and improve the repair mechanism on lymphocytes from melanoma patients. Importantly, no significant effect was observed in healthy lymphocytes when treated with the exosome concentrations at 24, 48 and 72 h. Comet assay results (OTM and %Tail DNA) demonstrated that the optimal exosome concentration showed a significant impact ( p < 0.05) in lymphocytes from melanoma patients whilst causing no significant DNA damage in lymphocytes of healthy volunteers was 300 μg/ml. Similarly, the Comet assay results depicted significant DNA damage in a melanoma cell line (CHL‐1 cells) treated with CBSC‐derived exosomes, both the cytotoxicity of CHL‐1 cells treated with CBSC‐derived exosomes exhibited a significant time‐dependent decrease in cell survival. Sequencing analysis of CBSC exosomes showed the presence of the let‐7 family of miRNAs, including let‐7a‐5p, let‐7b‐5p, let‐7c‐5p, let‐7d‐3p, let‐7d‐5p and two novel miRNAs. The potency of CBSC exosomes in inhibiting cancer progression in lymphocytes from melanoma patients and CHL‐1 cells whilst causing no harm to the healthy lymphocytes makes it a potential candidate as an anticancer therapy.